ОПТИМИЗАЦИЯ СИСТЕМ УПРАВЛЕНИЯ В СМАРТ-ГРИД ЭНЕРГОСЕТЯХ НА ОСНОВЕ ОБОБЩЕНИЯ ИНФОРМАЦИОННЫХ ПОТОКОВ - Никифоров, А.П. (Інститут електродинаміки НАН України, Київ, 2016)
A method of joint governance, hardware, electric power networks, relay protection and automation. The method is based on templates generic structures of parts of the information management system. Proposed description of structures criteria optimization. The method is focused on development in CAD of systems real-time. References 3, figures 3.